Immune modulation of metalloproteinase production in human macrophages. Selective pretranslational suppression of interstitial collagenase and stromelysin biosynthesis by interferon-gamma. - Shapiro, S D (1990)
Interferon-gamma (IFN-gamma) is a lymphokine that activates mononuclear phagocytes. To test the hypothesis that IFN-gamma might have important effects upon the ability of human mononuclear phagocytes to degrade extracellular matrix, we have studied the action of this cytokine on the production of metalloproteinases and the counterregulatory tissue inhibitor of metalloproteinases (TIMP) by the human alveolar macrophage. We have found that IFN-gamma potently and selectively suppresses the lipopolysaccharide-induced production of two metalloproteinases--interstitial collagenase and stromelysin--by 50-90% at doses greater than or equal to 10 U/ml. The synthesis of TIMP and 92-kD type IV collagenase was also diminished by IFN-gamma, but these responses required 50- to 100-fold higher concentrations of the cytokine. All doses of IFN-gamma increased total and secreted protein synthesis slightly, indicating a highly specific effect on metalloenzyme biosynthesis. Inhibition of metalloproteinase expression occurred at a pretranslational level, as evidenced by parallel reductions in enzyme biosynthesis and collagenase-specific steady-state mRNA levels. Interestingly, the effect of IFN-gamma on metalloenzyme production was not readily reversible. Therefore, while IFN-gamma activates the macrophage and renders it tumoricidal, this enhanced function appears to be attained at the expense of the cell's capacity to degrade extracellular matrix.